Improvement Sistem Pemenuhan dan Penyimpanan Seragam PT. XYZ - Setiawan, Octaviona Inge; Octavia, Tanti (Jurnal Titra, 2014)
Problem were found in a uniform warehouse in PT. XYZ are about uniform storage and overstock. This thesis give proposal to decrease uniform inventory cost and rearrange uniform warehouse. Propose for improvement which is given are uniform warehouse guideline with Kaizen concept, determine maximum inventory with Periodic Review, and guideline of uniform database. With Periodic Reviewâs method, the company can decrease percentage of stockout. Percentage of stockout is 3%.